Enantioselective nickel-catalyzed anti-carbometallative cyclizations of alkynyl electrophiles enabled by reversible alkenylnickel E/Z isomerization - Clarke, Christopher; Incerti-Pradillos, Celia A.; Lam, Hon Wai (American Chemical Society, 2016)
Nickel-catalyzed additions of arylboronic acids to alkynes, followed by enantioselective cyclizations of the alkenylnickel species onto tethered ketones or enones, are reported. These reactions are reliant upon the formal anti-carbonickelation of the alkyne, which is postulated to occur by the reversible E/Z isomerization of an alkenylnickel species.